1-butene-ethylene copolymer, 1-butene polymer composition containing said 1-butene-ethylene copolymer and a propylene polymer, 1-butene polymer composition containing said 1-butene-ethylene copolymer, a propylene polymer and an ethylene polymer, and uses thereof

JP7645988B2Active Publication Date: 2025-03-14MITSUI CHEMICALS INC

Patent Information

Application Number
JP2023505488
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-08
Filing Date
2022-03-03
Publication Date
2025-03-14
Estimated Expiration
2042-03-03

AI Technical Summary

Benefits of technology

【0011】 本発明の1-ブテン·エチレン共重合体(A)は、結晶化速度が遅く、且つ低結晶性でありながら、強度、成形性のバランスに優れ、柔軟性が良好であるので、例えば、不織布の改質材やホットメルト接着剤に好適に用い得る。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007645988000001
    Figure 0007645988000001
  • Figure 0007645988000002
    Figure 0007645988000002
  • Figure 0007645988000003
    Figure 0007645988000003
Patent Text Reader

Abstract

The purpose of the present invention is to develop a 1-butene / ethylene copolymer which has an excellent balance between strength and fluidity while having a slow crystallization speed and low crystallinity, has excellent compatibility with a propylene-based copolymer, and can exhibit excellent heat resistance when combined with a propylene-based resin. The present invention pertains to a 1-butene / ethylene copolymer (A) satisfying the following requirements (A1)-(A5). (A1) The content of a constitutional unit (i) derived from 1-butene is in the range of 70-99.9 mol%, and the content of a constitutional unit (ii) derived from ethylene is in the range of 0.1-30 mol% [where the total amount of the constitutional unit (i) and constitutional unit (ii) is 100 mol%]. (A2) The isotactic pentad fraction (mmmm) calculated by 13C-NMR is in the range of 80-99.9%. (A3) The intrinsic viscosity [η] in a decalin solvent at 135ºC is in the range of 0.7-2.0 dl / g. (A4) The melt flow rate (MFR), which is measured at 190ºC under a load of 2.16 kg in accordance with ASTM D1238, is in the range of 1-100 g / 10 min. (A5) In calorimetry with a differential scanning calorimeter (DSC), a melting peak is not observed during a second temperature rise.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a 1-butene-ethylene copolymer having a specific composition and specific properties, a 1-butene polymer composition containing the 1-butene-ethylene copolymer and a propylene-based polymer, and a 1-butene polymer composition containing the 1-butene-ethylene copolymer, a propylene-based polymer and an ethylene-based polymer, and uses of the same. [Background technology]

[0002] 1-Butene polymers have excellent creep properties at high temperatures, abrasion resistance, flexibility, and compatibility with polypropylene, and are therefore used to modify water and hot water supply pipes, sheets for skins, polypropylene resins, hot melt adhesives, etc.

[0003] Patent Document 1 proposes a resin modifier composed of a highly fluid 1-butene polymer having a good balance of fluidity, tensile modulus and elongation, and secondary processability, the polymer having an intrinsic viscosity [η] in a range of 0.01 to 0.5 dl / g measured in a tetralin solvent at 135°C, a melting point in a range of 0 to 100°C measured using a differential scanning calorimeter (DSC), and a stereoregularity index {(mmmm) / (mmrr+rmmr)} of 30 or less, and a hot melt adhesive containing the 1-butene polymer.

[0004] Patent Document 2 also proposes a hot melt adhesive containing a 1-butene copolymer that contains 2 to 6% by weight of ethylene derived units and has a high melt flow rate of 200 to 1500 when measured in accordance with ISO1133 (190°C, 2.16 kg).

[0005] However, 1-butene polymers with reduced stereoregularity, or 1-butene copolymers obtained by copolymerizing 1-butene with an α-olefin, have the problem of reduced strength and heat resistance. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 03 / 070788 Brochure [Patent Document 2] Special Publication No. 2017-504667 Summary of the Invention [Problem to be solved by the invention]

[0007] The objective of the present invention is to develop a 1-butene-ethylene copolymer that has a slow crystallization rate and low crystallinity, while having an excellent balance between strength and fluidity. [Means for solving the problem]

[0008] The present invention relates to a 1-butene-ethylene copolymer (A) that satisfies the following requirements (A1) to (A5). (A1) The content of structural units (i) derived from 1-butene is in the range of 70 to 99.9 mol %, and the content of structural units (ii) derived from ethylene is in the range of 0.1 to 30 mol % (wherein the total of structural units (i) and (ii) is 100 mol %). (A2) 13 The isotactic pendant fraction (mmmm) calculated by C-NMR is in the range of 80 to 99.9%. (A3) The intrinsic viscosity [η] in decalin solvent at 135°C is in the range of 0.7 to 2.0 dl / g. (A4) The melt flow rate (MFR) measured in accordance with ASTM D1238 at 190°C under a load of 2.16 kg is in the range of 1 to 100 g / 10 min. (A5) Using a differential scanning calorimeter (DSC), the temperature is increased from -70°C to 200°C at a heating rate of 20°C / min (first heating), and then held at 200°C for 10 minutes. Thereafter, the temperature is decreased to -70°C at a cooling rate of 20°C / min (first heating), and held at -70°C for 1 minute. After that, the temperature is increased again from -70°C to 200°C at a heating rate of 20°C / min (second heating), and no melting peak is observed during the second heating.

[0009] The present invention also relates to a 1-butene polymer composition comprising a 1-butene-ethylene copolymer (A) satisfying the following requirements (A1) to (A5) and a propylene polymer (B) satisfying the following requirements (B1) and (B2): (A1) When the total of the structural unit (i) derived from 1-butene and the structural unit (ii) derived from ethylene is taken as 100 mol %, the content of the structural unit (i) is in the range of 70 to 99.9 mol %, and the content of the structural unit (ii) is in the range of 0.1 to 30 mol %. (A2) 13 The isotactic pendant fraction (mmmm) calculated by C-NMR is in the range of 80 to 99.9%. (A3) The intrinsic viscosity [η] in decalin solvent at 135°C is in the range of 0.7 to 2.0 dl / g. (A4) The melt flow rate (MFR) measured in accordance with ASTM D1238 at 190°C under a load of 2.16 kg is in the range of 1 to 100 g / 10 min. (A5) Using a differential scanning calorimeter (DSC), the temperature is increased from -70°C to 200°C at a heating rate of 20°C / min (first heating), and then held at 200°C for 10 minutes. Thereafter, the temperature is decreased to -70°C at a cooling rate of 20°C / min (first heating), and held at -70°C for 1 minute. After that, the temperature is increased again from -70°C to 200°C at a heating rate of 20°C / min (second heating), and no melting peak is observed during the second heating. (B1) The melting point measured by a differential scanning calorimeter is in the range of 100 to 170°C. (B2) The isotactic pentad fraction is in the range of 90 to 99.9%.

[0010] The present invention further relates to a 1-butene polymer composition containing a 1-butene-ethylene copolymer (A) and a propylene polymer (B), which satisfies the following requirement (X4): (X4) The Shore D hardness measured in accordance with ASTM D2240 is in the range of 20 to 80. Effect of the Invention

[0011] The 1-butene-ethylene copolymer (A) of the present invention has a slow crystallization rate and low crystallinity, yet has an excellent balance between strength and moldability and good flexibility, and can therefore be suitably used, for example, as a modifier for nonwoven fabrics or a hot melt adhesive.

[0012] In addition, since the 1-butene-ethylene copolymer (A) has good compatibility with the propylene polymer (B), the 1-butene polymer composition of the present invention containing the propylene polymer (B) can provide a butene polymer composition capable of forming a molded product having excellent flexibility and excellent whitening resistance during stretching. In addition, the composition exhibits excellent heat resistance and good transparency, and can be suitably used for hot melt adhesives and packaging materials. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] <1-butene-ethylene copolymer (A)> The 1-butene-ethylene copolymer (A) of the present invention and the 1-butene-ethylene copolymer (A) which is one of the components of the 1-butene polymer composition of the present invention are 1-butene-ethylene copolymers (A) which satisfy the following requirements (A1) to (A5). (A1) The content of structural units (i) derived from 1-butene is in the range of 70 to 99.9 mol %, and the content of structural units (ii) derived from ethylene is in the range of 0.1 to 30 mol % (wherein the total of structural units (i) and (ii) is 100 mol %).

[0014] In the 1-butene-ethylene copolymer (A) of the present invention, the lower limit of the amount of structural units derived from 1-butene is 70 mol %. Amount The lower limit is preferably 75 mol %, more preferably 80 mol %, and particularly preferably 85 mol %.

[0015] On the other hand, the upper limit of the amount of structural units derived from 1-butene is 99.9 mol%, preferably 98 mol%, more preferably 96 mol%, even more preferably 95 mol%, and particularly preferably 90.5 mol%.

[0016] In the 1-butene-ethylene copolymer (A) of the present invention, the upper limit of the amount of the structural unit (ii) derived from ethylene is 30 mol %. Amount The upper limit is preferably 25 mol %, more preferably 20 mol %, and particularly preferably 15 mol %.

[0017] On the other hand, the lower limit of the amount of the structural unit (ii) derived from ethylene is 0.1 mol%, preferably 2 mol%, more preferably 4 mol%, even more preferably 5 mol%, and particularly preferably 9.5 mol%.

[0018] The 1-butene-ethylene copolymer (A) of the present invention can have good compatibility with the propylene polymer (B) described below by adjusting the amount of the structural unit (ii) derived from ethylene to within the above range. The amount When it is equal to or less than the upper limit, the mechanical strength is excellent, and when it is used as a hot melt adhesive, for example, it is preferable in terms of excellent adhesive strength, and when it is used as a packaging material, it is preferable because the durability of the film is improved. When it is equal to or more than the lower limit, the crystallization speed is appropriate, and when it is used as a modifier for nonwoven fabric, for example, it is preferable because the molding conditions for stable spinning are expanded and moldability is improved, when it is used as a hot melt adhesive, it is preferable because the feature of the present invention, that is, the long open time, can be fully exhibited, and when it is used as a packaging material, it is preferable because it has excellent whitening resistance during stretching when combined with a propylene-based polymer.

[0019] The content (mol %) of each of the structural units constituting the 1-butene-ethylene copolymer (A) is 13 The measurement is performed by C-NMR. Details of the measurement method are as described in the Examples below. (A2) 13 The isotactic pendant fraction (mmmm) calculated by C-NMR is in the range of 80 to 99.9%.

[0020] In the 1-butene-ethylene copolymer (A) of the present invention, the lower limit of the isotactic pentad fraction (mmmm) is preferably 85%, more preferably 90%. The upper limit of the isotactic pentad fraction (mmmm) is preferably 99.5%, more preferably 99.0%. By setting the isotactic pentad fraction (mmmm) within the above range, it becomes possible to design appropriate mechanical strength and flexibility even when ethylene is copolymerized and the compatibility with the propylene-based copolymer (B) described below is controlled.

[0021] Details of the method for measuring the isotactic pentad fraction (mmmm) are as described in the Examples section below. (A3) The intrinsic viscosity [η] in decalin solvent at 135°C is in the range of 0.7 to 2.0 dl / g.

[0022] 1-Butene-ethylene copolymer (A) of the present invention Intrinsic viscosity [η] is 0.8 to 1.9 dl / g More preferably, the ratio is 0.9 to 1.85. dl / g More preferably, the ratio is 1.0 to 1.8. dl / g The 1-butene / ethylene copolymer (A) having an intrinsic viscosity [η] within the above range has an excellent balance between fluidity and mechanical strength.

[0023] For example, adhesives such as hot melt adhesives containing 1-butene-ethylene copolymer (A) have good handling properties and are suitable for high-speed application. In addition, molded products with excellent mechanical properties can be easily obtained, and they are preferable because they can be easily molded and have both excellent durability as packaging materials. (A4) The melt flow rate (MFR) measured in accordance with ASTM D1238 at 190°C under a load of 2.16 kg is in the range of 1 to 100 g / 10 min, preferably 2 to 90 g / 10 min, more preferably 3 to 85 g / 10 min, and even more preferably 3.2 to 80 g / 10 min.

[0024] When the MFR is within the above range, the fluidity is good, and the obtained molded article has good mechanical properties. For example, adhesives such as hot melt adhesives containing 1-butene-ethylene copolymer (A) have good handling properties and are suitable for high-speed application. When used as a hot melt adhesive, high fluidity is required, so it is particularly preferable that the MFR is in the range of 18 to 80 g / 10 min. In addition, molded articles with excellent mechanical properties can be easily obtained. When used in molded articles such as packaging materials, it is particularly preferable that the MFR is 15 g / 10 min or less, taking into consideration the balance between fluidity and mechanical properties appropriate for the molding machine.

[0025] When the MFR is above the lower limit, the adhesive has fluidity, and the adhesive, such as a hot melt adhesive containing 1-butene-ethylene copolymer (A), has good handleability and is suitable for high-speed application. When the MFR is below the upper limit, the mechanical properties of 1-butene-ethylene copolymer (A) are excellent, and the adhesive containing 1-butene-ethylene copolymer (A) is preferable from the viewpoints of adhesive strength, oil resistance, and creep resistance, and is preferable because it has excellent durability when used as a packaging material. (A5) In calorimetry using a differential scanning calorimeter (DSC), no melting peak is observed during the second heating period.

[0026] In the present invention, calorimetry using a differential scanning calorimeter (DSC) involves precisely weighing out about 6 to 10 mg of a sample, sealing it in an aluminum pan, heating it from -70°C to 200°C at a heating rate of 20°C / min (first heating), measuring a DSC curve, holding it at 200°C for 10 minutes, then lowering the temperature to -70°C at a cooling rate of 20°C / min (first heating), measuring a DSC curve, holding it at -70°C for 1 minute, and then again heating it from -70°C to 200°C at a heating rate of 20°C / min (second heating), measuring a DSC curve.

[0027] In this specification, the melting peak is measured by the measurement method described above, the melting point refers to the temperature at the peak apex of the melting peak, and the absence of melting peak means that no crystal melting peak with a crystal melting enthalpy of 1 J / g or more is observed. Note that, when two or more melting peaks are observed, the lowest temperature among the peak apex temperatures of these peaks is the melting point.

[0028] In addition to the above requirements (A1) to (A5), the 1-butene-ethylene copolymer (A) of the present invention preferably has a melting point (Tm) measured at the first heating stage by a differential scanning calorimeter (DSC) of 70°C or lower, more preferably 65°C or lower.

[0029] In addition to the above requirements (A1) to (A5), the 1-butene-ethylene copolymer (A) of the present invention preferably has a melting enthalpy of 1 to 60 J / g, more preferably 2 to 50 J / g, as measured in the first temperature rise of a differential scanning calorimeter (DSC). The melting enthalpy is an index of the degree of crystallinity. When the melting enthalpy is equal to or less than the upper limit, the crystallinity is low, the flexibility is excellent, and the flexibility and deformation followability as a hot melt adhesive are improved. When the melting enthalpy is equal to or more than the lower limit, the mechanical properties are excellent, and the adhesive strength as a hot melt adhesive is improved. When the melting enthalpy is within the above range, the flexibility and low stickiness are well balanced.

[0030] The fact that a melting peak is observed during the first heating and that no melting peak is observed during the second heating, despite the fact that the copolymer has crystallinity, indicates that the crystallization rate of 1-butene-ethylene copolymer (A) is extremely slow. This means that when 1-butene-ethylene copolymer (A) is used as a modifier for nonwoven fabrics, the nonwoven fabrics are favorable because the molding conditions for stable spinning are expanded and the moldability is improved. In addition, when used as an adhesive, it has excellent adhesive strength after solidification and can extend the open time during application.

[0031] In addition to the above requirements (A1) to (A5), the 1-butene-ethylene copolymer (A) of the present invention preferably has (A6) a weight average molecular weight (Mw) of 100,000 to 400,000.

[0032] When flowability is required, the weight average molecular weight is more preferably 100,000 to 400,000, even more preferably 100,000 to 390,000, and particularly preferably 100,000 to 380,000. When the weight average molecular weight is within the above range, the adhesive such as a hot melt adhesive containing the 1-butene-ethylene copolymer (A) has good handleability and is suitable for high-speed application. When mechanical strength is required, the weight average molecular weight (Mw) is more preferably 110,000 to 380,000, even more preferably 120,000 to 380,000, and particularly preferably 132,000 to 380,000. When the weight average molecular weight is within the above range, a molded product having excellent mechanical properties can be easily obtained. When used as a hot melt adhesive, the adhesive strength is improved.

[0033] Furthermore, the molecular weight distribution (Mw / Mn) is preferably 1.5 to 3.0, more preferably 1.6 to 2.8. Mw / Mn is a value calculated as polystyrene measured by a GPC method. A 1-butene-ethylene copolymer (A) having an Mw / Mn in the above range is preferable because it contains less low molecular weight components that reduce mechanical strength and less high molecular weight components that deteriorate flowability.

[0034] In addition to the above requirements (A1) to (A5), the 1-butene-ethylene copolymer (A) of the present invention preferably has requirement (A7) that the maximum value of Shore A hardness (based on ASTM D2244) is 70 to 99, or requirement (A8) that the maximum value of Shore D hardness (based on ASTM D2244) is 20 to 70. A more preferred range of Shore A hardness is 75 to 98. A more preferred range of Shore D hardness is 25 to 65. The Shore A hardness or Shore D hardness is an index of crystallinity. When the Shore A hardness or Shore D hardness is equal to or less than the upper limit, a molded product having low crystallinity and excellent flexibility and whitening resistance during stretching can be easily obtained. In addition, when used as a hot melt adhesive, flexibility and deformation followability are improved. When the Shore A hardness or Shore D hardness is equal to or more than the lower limit, a molded product having excellent mechanical properties can be easily obtained. In addition, when used as a hot melt adhesive, adhesive strength is improved.

[0035] <Production method of 1-butene-ethylene copolymer (A)> The 1-butene-ethylene copolymer (A) of the present invention can be obtained, for example, by polymerizing monomers in the presence of a catalyst such as a Ziegler-Natta catalyst or a metallocene catalyst by a known polymerization method such as a gas phase method, a bulk method, or a slurry method. Among them, it is preferable to use a metallocene catalyst that can uniformly control the reaction, because it not only enables the design of a molded product having a narrow molecular weight distribution and composition distribution and an excellent balance between mechanical strength and flexibility, but also provides good compatibility when combined with a propylene polymer (B) described below, and enables the delay of the crystallization rate in hot melt adhesives. Polymerization using a metallocene compound represented by the following general formula (1) or (2) is particularly preferable.

[0036] [ka]

[0037] [ka] R in the above general formula (1) or (2) 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 , R 9 , R 10 , R 11 , R 12 are selected from hydrogen, hydrocarbon groups, and silicon-containing hydrocarbon groups, and may be the same or different.

[0038] The hydrocarbon group is preferably an alkyl group having 1 to 20 carbon atoms, an arylalkyl group having 7 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, or an alkylaryl group having 7 to 20 carbon atoms, which may contain one or more ring structures. Specific examples thereof include methyl, ethyl, n-propyl, isopropyl, 2-methylpropyl, 1,1-dimethylpropyl, 2,2-dimethylpropyl, 1,1-diethylpropyl, 1-ethyl-1-methylpropyl, 1,1,2,2-tetramethylpropyl, sec-butyl, tert-butyl, etc.

[0039] The silicon-containing hydrocarbon group is preferably an alkylsilyl group or arylsilyl group having 1 to 4 silicon atoms and 3 to 20 carbon atoms, and specific examples thereof include trimethylsilyl, tert-butyldimethylsilyl, and triphenylsilyl.

[0040] In addition, R 2 is preferably a sterically bulky hydrocarbon group or a silicon-containing hydrocarbon group, i.e., a secondary or tertiary substituent, more preferably a substituent having 4 or more carbon atoms. base Examples of the butyl ether include isopropyl, 1,1-dimethylpropyl, 1,1-diethylpropyl, 1-ethyl-1-methylpropyl, 1,1,2,2-tetramethylpropyl, sec-butyl, tert-butyl, and 1,1-dimethylbutyl. Tert-butyl is particularly preferred. Silicon-containing hydrocarbons baseExamples of the compounds include those in which some or all of the carbon atoms in the above compounds are substituted with silicon atoms.

[0041] R on the fluorene ring 5 From R 12 Adjacent substituents up to may be bonded to each other to form a ring. Examples of such substituted fluorenyl groups include benzofluorenyl and dibenzofluorenyl. In addition, R on the fluorene ring 5 From R 12 The substituents are symmetrical for ease of synthesis, i.e., R 5 =R 12 , R 6 =R 11 , R 7 =R 10 , R 8 =R 9 Preferably, the fluorene ring is unsubstituted, 3,6-disubstituted, 2,7-disubstituted, or 2,3,6,7-tetrasubstituted, and more preferably, the fluorene ring is unsubstituted, 3,6-disubstituted, 2,7-disubstituted, or 2,3,6,7-tetrasubstituted. 7 , R 10 , R 6 , R 11 R in the above general formula (1) 3 and R 4 are selected from hydrogen and hydrocarbon groups, and may be the same or different. Specific examples of preferred hydrocarbon groups include those mentioned above. Y is carbon or silicon. In the case of general formula (1), R 13 and R 14 is bonded to Y to form a substituted methylene group or a substituted silylene group as a bridging moiety. Preferred specific examples include methylene, dimethylmethylene, diisopropylmethylene, methyl tert-butylmethylene, dicyclohexylmethylene, methylcyclohexylmethylene, methylphenylmethylene, diphenylmethylene, dimethylsilylene, diisopropylsilylene, etc. More preferably, Y is carbon.

[0042] R in general formula (1) or (2) 2 When is a tert-butyl group, R 1is preferably a methyl or ethyl group, and more preferably a methyl group. 3 , R 4 is a methyl or phenyl group, preferably a methyl group. 3 , R 4 It is preferable that R in the general formula (1) is the same as each other. 2 is a tert-butyl group, R 1 When is a methyl group, R 5 ~R 12 may be hydrogen.

[0043] Furthermore, R 2 is a tert-butyl group, R 1 When is an ethyl group, R 5 , R 7 , R 8 , R 9 , R 10 , R 12 is hydrogen and R 6 , R 11 is preferably a tert-butyl group.

[0044] In the case of general formula (2), Y is bonded to a divalent hydrocarbon group A having 2 to 20 carbon atoms, which may contain a partially unsaturated bond and / or an aromatic ring, to form a cycloalkylidene group, a cyclomethylenesilylene group, etc. Preferable specific examples include cyclopropylidene, cyclobutylidene, cyclopentylidene, cyclohexylidene, etc.

[0045] M in the general formulas (1) and (2) is a metal selected from Group 4 of the periodic table, and examples of M include titanium, zirconium, and hafnium. Q is selected from halogens, hydrocarbon groups having 1 to 20 carbon atoms, anionic ligands, and neutral ligands capable of coordinating with lone electron pairs, in the same or different combinations. Specific examples of halogens include fluorine, chlorine, bromine, and iodine, and specific examples of hydrocarbon groups include those described above. Specific examples of anionic ligands include alkoxy groups such as methoxy, tert-butoxy, and phenoxy, carboxylate groups such as acetate and benzoate, and sulfonate groups such as mesylate and tosylate. Specific examples of neutral ligands capable of coordinating with lone electron pairs include organic phosphorus compounds such as trimethylphosphine, triethylphosphine, triphenylphosphine, and diphenylmethylphosphine, and ethers such as tetrahydrofuran, diethyl ether, dioxane, and 1,2-dimethoxyethane. Among these, Q may be the same or different in combination, but at least one is preferably a halogen or an alkyl group.

[0046] The component (C) is an organoaluminum oxy compound (C-1), a compound (C-2) which reacts with the metallocene compound (A) to form an ion pair, and an organoaluminum compound (C-3) At least one compound selected from Things If necessary, the carrier may further comprise a particulate carrier (D).

[0047] As the organoaluminum oxy compound (C-1) used, a conventionally known aluminoxane can be used as it is. Examples of the compound (C-2) (hereinafter sometimes abbreviated as "ionic compound") that reacts with the metallocene compound (A) to form an ion pair include Lewis acids, ionic compounds, borane compounds, and carborane compounds described in JP-A-1-501950 and JP-A-2004-51676, etc. Furthermore, heteropoly compounds and isopoly compounds can also be mentioned.

[0048] Specific examples include triphenylboron, tris(o-tolyl)boron, tris(p-tolyl)boron, tris(3,5-dimethylphenyl)boron, trimethylboron, triisobutylboron; compounds having a halogen-containing aryl group, such as compounds having a fluorine-containing aryl group, such as tris(4-fluorophenyl)boron, tris(3,5-difluorophenyl)boron, tris(4-fluoromethylphenyl)boron, and tris(pentafluorophenyl)boron; and trifluoroboron.

[0049] As the organoaluminum compound (C-3) which forms an olefin polymerization catalyst, for example, there can be mentioned an organoaluminum compound represented by the following general formula (3). RamAl(ORb)HpQq (3) (In the formula, Ra and Rb may be the same or different and each represent a hydrocarbon group having 1 to 15, preferably 1 to 4, carbon atoms; Q represents a halogen atom; m represents 0. <m≦3 、p p is a number 0≦p<3, q is a number 0≦q<3, and m +p +q=3. Specific examples of such compounds include dialkylaluminum hydrides such as trimethylaluminum, triethylaluminum, tri-n-butylaluminum, diisopropylaluminum hydride, and diisobutylaluminum hydride, and alkylaluminum alkoxides such as isobutylaluminum methoxide and isobutylaluminum ethoxide.

[0050] As the organoaluminum compound (C-3), tri-n-alkylaluminums such as trimethylaluminum, triethylaluminum, and trioctylaluminum, and tri-branched alkylaluminums such as triisobutylaluminum are preferred, with trimethylaluminum and triisobutylaluminum being particularly preferred.

[0051] In the present invention, the polymerization of 1-butene-ethylene copolymer (A) can be carried out by either liquid phase polymerization such as solution polymerization or suspension polymerization, or gas phase polymerization. In the liquid phase polymerization, an inert hydrocarbon solvent may be used, specifically, aliphatic hydrocarbons such as propane, butane, pentane, hexane, heptane, octane, decane, etc.; alicyclic hydrocarbons such as cyclopentane, cyclohexane, methylcyclopentane, etc.; aromatic hydrocarbons such as benzene, toluene, xylene, etc., or mixtures thereof. Bulk polymerization can also be carried out using olefins containing 1-butene as the solvent.

[0052] In carrying out the polymerization, component (A) is usually used in an amount of 10 -8 ~10 -2 Molar, preferably 10 -7 ~10 -3 Component (C-1) is used in an amount such that the molar ratio of component (C-1) to the transition metal atom (M) in component (A) [(C-1) / M] is usually 0.01 to 5000, preferably 0.05 to 2000. Component (C-2) is used in an amount such that the molar ratio of component (C-2) to the transition metal atom (M) in component (A) [(C-2) / M] is usually 1 to 10, preferably 1 to 5. Component (C-3) is used in an amount such that the molar ratio of component (C-3) to the transition metal atom (M) in component (A) [(C- 3 ) / M] is usually from 10 to 5,000, preferably from 20 to 2,000.

[0053] The polymerization temperature is usually in the range of −50 to 200° C., preferably 0 to 100° C., and more preferably 20 to 100° C. If the polymerization temperature is too low, it tends to be industrially disadvantageous in terms of polymerization activity per unit catalyst and heat recovery efficiency.

[0054] The polymerization pressure is usually normal pressure to 10 MPa gauge pressure, preferably normal pressure to 5 MPa gauge pressure, and the polymerization reaction can be carried out by any of batch, semi-continuous, and continuous methods. Furthermore, the polymerization can be carried out in two or more stages with different reaction conditions.

[0055] Hydrogen can be added to control the molecular weight and polymerization activity of the 1-butene-ethylene copolymer (A) produced during polymerization. The appropriate amount of hydrogen is about 0.001 to 100 nL per kg of 1-butene-ethylene copolymer (A).

[0056] <Propylene-based polymer (B)> The propylene polymer (B), which is one of the components of the 1-butene polymer composition of the present invention, is a propylene polymer (B) that satisfies the following requirements (B1) and (B2). (B1) The melting point measured by a differential scanning calorimeter is in the range of 100 to 170°C, preferably 130 to 170°C.

[0057] The 1-butene polymer composition containing the propylene polymer (B) having a melting point within the above range exhibits excellent heat resistance, has good transparency and has an appropriately slow crystallization rate. (B2) The isotactic pentad fraction (mmmm) is in the range of 80 to 99.9%, preferably 85 to 99.9%, and more preferably 90 to 99.9%.

[0058] A 1-butene polymer composition containing a propylene polymer (B) having an isotactic pentad fraction (mmmm) that satisfies the above range has an appropriately slow crystallization rate and is preferable in terms of open time as a hot melt adhesive.

[0059] The propylene polymer (B) according to the present invention preferably satisfies the following requirement (B3) in addition to the requirements (B1) and (B2). (B3) The crystallization temperature is in the range of 40°C to 120°C, preferably 60 to 120°C, and more preferably 80 to 120°C.

[0060] When the crystallization temperature of the propylene polymer (B) according to the present invention is equal to or lower than the upper limit, the degree of crystallization of the 1-butene copolymer composition is not too high and has an appropriate crystallization rate, so that when used as a hot melt adhesive, it is possible to have a long open time, which is the object of the present invention, and this is preferable. On the other hand, when the crystallization temperature of the propylene polymer (B) is equal to or higher than the lower limit, the degree of crystallization is not too low, so this is preferable from the viewpoints of mechanical strength and heat resistance.

[0061] The crystallization temperature of the propylene polymer (B) according to the present invention was determined as the peak observed in the first temperature drop process using a differential scanning calorimeter. In addition to the above requirements (B1) to (B3), the propylene polymer (B) according to the present invention preferably has a melt flow rate (MFR) measured at a temperature of 230° C. under a load of 2.16 kg in the range of 0.1 to 150 g / 10 min, more preferably 1 to 100 g / 10 min, further preferably 2 to 100 g / 10 min, and particularly preferably 3 to 50 g / 10 min.

[0062] When the MFR is equal to or higher than the lower limit, the polymer has flowability and exhibits good compatibility with other polymers including the 1-butene-ethylene copolymer (A). Adhesives such as hot melt adhesives containing the propylene polymer (B) have good handleability and are suitable for high-speed application. When the MFR is equal to or lower than the upper limit, the propylene polymer (B) exhibits excellent mechanical properties, and molded articles containing the propylene polymer (B) exhibit excellent mechanical strength and impact resistance. For example, when used as an adhesive, this is preferable from the viewpoints of adhesive strength, heat resistance, and creep resistance.

[0063] The propylene polymer (B) according to the present invention may be a propylene homopolymer or a copolymer of propylene and at least one α-olefin other than propylene having 2 to 20 carbon atoms. Examples of the α-olefin other than propylene having 2 to 20 carbon atoms include ethylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene, and ethylene or an α-olefin having 4 to 10 carbon atoms is preferred.

[0064] The copolymer of propylene with these α-olefins may be a random copolymer or a block copolymer. The constituent units derived from these α-olefins may be contained in the copolymer of α-olefins and propylene in a proportion of 35 mol % or less, preferably 30 mol % or less.

[0065] The method for producing the propylene polymer (B) according to the present invention is not particularly limited, and examples thereof include well-known methods using well-known catalysts such as Ziegler-Natta catalysts and metallocene catalysts.

[0066] <Ethylene-based polymer (C)> The 1-butene polymer composition of the present invention may further contain an ethylene polymer (C). The ethylene polymer (C) contains 60 to 100 mol % of structural units derived from ethylene. Specific examples of the ethylene polymer (C) according to the present invention include high-pressure low-density polyethylene (C1) and ethylene-α-olefin copolymer (C2).

[0067] By using the ethylene polymer (C), the resulting 1-butene polymer composition can easily give a molded article having a good balance between excellent impact resistance and transparency. <High-pressure low-density polyethylene (C1)> Any known high-pressure low-density polyethylene can be used without restriction as the high-pressure low-density polyethylene (C1). The high-pressure low-density polyethylene is generally obtained by radical polymerization of ethylene under high temperature and high pressure, and the method for producing it is not particularly limited, but includes, for example, a radical polymerization method in which radical polymerization is performed under conditions of 500 to 2000 atmospheric pressure and 150 to 300°C, and the polymerization initiator here includes, for example, an organic peroxide.

[0068] High-pressure low-density polyethylene (C1) has a density of 900 to 925 kg / m3 as measured in accordance with ASTM D1505. 3 and more preferably in the range of 910 to 925 kg / m 3 It is.

[0069] The high-pressure low-density polyethylene (C1) has a melt flow rate (MFR), measured in accordance with ASTM D1238 at 190°C under a load of 2.16 kg, of preferably 0.1 g / 10 min or more, more preferably 0.5 g / 10 min or more, particularly preferably 1.0 g / 10 min or more, and preferably 50 g / 10 min or less, more preferably 30 g / 10 min or less, particularly preferably 20 g / 10 min or less. Ethylene-α-olefin copolymer (C2) The ethylene-α-olefin copolymer (C2) contains at least structural units derived from ethylene and structural units derived from an α-olefin having 3 to 20 carbon atoms.

[0070] The content of structural units derived from ethylene in the ethylene-α-olefin copolymer (C2) is 60 to 99 mol %, preferably 65 to 99 mol %, more preferably 70 to 99 mol %, and particularly preferably 80 to 99 mol %.

[0071] Ethylene-α-olefin copolymer (C2) is characterized by having fewer long-chain branched structures compared to high-pressure low-density polyethylene (C1), and is generally referred to as linear low-density polyethylene (LLDPE).

[0072] The content of structural units derived from an α-olefin having 3 to 20 carbon atoms in the ethylene-α-olefin copolymer (C2) is 1 to 40 mol %, preferably 1 to 35 mol %, more preferably 1 to 30 mol %, and particularly preferably 1 to 20 mol %.

[0073] These contents are based on 100 mol % in total of the structural units derived from ethylene and the α-olefin having 3 to 20 carbon atoms. When the content of the structural units is within the above range, a molded article having a good balance between impact resistance and flexibility can be easily obtained.

[0074] Examples of the α-olefin having 3 to 20 carbon atoms include propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-nonadecene, and 1-eicosene. Among these, α-olefins having 3 to 10 carbon atoms are preferred, α-olefins having 3 to 8 carbon atoms are more preferred, propylene, 1-butene, and 1-octene are even more preferred, and propylene is particularly preferred.

[0075] The α-olefins having 3 to 20 carbon atoms may be used alone or in combination of two or more kinds. The ethylene / α-olefin copolymer (C2) may contain, in addition to the above-mentioned structural units, one or more structural units derived from other polymerizable monomers, within the scope of the present invention.

[0076] Examples of such other polymerizable monomers include vinyl compounds such as styrene, vinylcyclopentene, vinylcyclohexane, and vinylnorbornane; vinyl esters such as vinyl acetate; unsaturated organic acids or derivatives thereof such as maleic anhydride; and non-conjugated polyenes such as dicyclopentadiene, cyclohexadiene, and 5-ethylidene-2-norbornene.

[0077] Specific examples of the ethylene-α-olefin copolymer (C2) include ethylene-propylene copolymer, ethylene-1-butene copolymer, ethylene-propylene-1-butene copolymer, ethylene-propylene-ethylidenenorbornene copolymer, ethylene-1-butene-1-octene copolymer, ethylene-4-methyl-1-pentene copolymer, ethylene-1-hexene copolymer, and ethylene-1-octene copolymer. Among these, for example, ethylene-propylene copolymer and ethylene-1-butene copolymer are preferred.

[0078] The density of the ethylene-α-olefin copolymer (C2) is preferably 840 kg / m 3 More preferably, 850 kg / m 3 More preferably, 855 kg / m 3 or more, preferably 940 kg / m 3 Less than or equal to 899 kg / m 3 Less than 890 kg / m, more preferably 890 kg / m 3 Less than 885 kg / m 3 The following is the result.

[0079] When the density is within the above range, a molded article having a good balance of impact resistance, rigidity and transparency can be easily obtained. The density can be measured by a density gradient tube method.

[0080] The MFR of the ethylene-α-olefin copolymer (C2) (measured in accordance with ASTM D1238 at 190°C under a load of 2.16 kg) is preferably 0.01 g / 10 min or more, more preferably 0.1 g / 10 min or more, and is preferably 40 g / 10 min or less, more preferably 20 g / 10 min or less, particularly preferably 10 g / 10 min or less.

[0081] When the MFR is within the above range, a molded article having excellent balance of impact resistance, rigidity and transparency can be easily obtained. Ethylene-α-olefin copolymer (C2) has an MFR measured at 190°C under a load of 10 kg in accordance with ASTM D1238. 10 and MFR measured at 190℃ and a load of 2.16 kg 2 Ratio to (MFR 10 / MFR 2 ) is preferably 4.0 or more, more preferably 5.0 or more, and is preferably 8.0 or less, more preferably 7.0 or less.

[0082] MFR 10 / MFR 2 When the amount of the resin is within the above range, a molded article having a good balance between transparency and impact resistance can be easily obtained. The ethylene-α-olefin copolymer (C2) can be produced by a conventional method using a vanadium catalyst, a titanium catalyst, a metallocene catalyst, etc. Preferably, the copolymer is produced using a metallocene catalyst, which allows the production of a copolymer having a narrow molecular weight distribution and composition distribution, and is more preferable in terms of mechanical properties, transparency, and impact resistance.

[0083] <1-Butene polymer composition> The 1-butene polymer composition of the present invention is a composition containing the 1-butene-ethylene copolymer (A), the propylene polymer (B), and, if necessary, the ethylene polymer (C). Examples of the 1-butene polymer composition include a composition containing the 1-butene-ethylene copolymer (A) and the propylene polymer (B), a composition containing the 1-butene-ethylene copolymer (A), the propylene polymer (B), and the high-pressure low-density polyethylene (C1), a composition containing the 1-butene-ethylene copolymer (A), the propylene polymer (B), and the ethylene-α-olefin copolymer (C2), and a composition containing the 1-butene-ethylene copolymer (A), the propylene polymer (B), the high-pressure low-density polyethylene (C1), and the ethylene-α-olefin copolymer (C2).

[0084] The 1-butene polymer composition of the present invention is preferably a 1-butene polymer composition that satisfies the following requirement (X4), and more preferably satisfies one or more of the following requirements (X1), (X2) and (X3). [Requirement (X1)] As a preferred embodiment of the present invention, (X1-1) a 1-butene polymer composition having a 1-butene-ethylene copolymer (A) content in the range of 63 to 99 mass% and a propylene polymer (B) content in the range of 1 to 37 mass% (wherein the total of the 1-butene-ethylene copolymer (A) and the propylene polymer (B) is 100 mass%); (X1-2) a 1-butene polymer composition having a 1-butene-ethylene copolymer (A) content in the range of 1 to 62 mass% and a propylene polymer (B) content in the range of 38 to 99 mass% (wherein the total of the 1-butene-ethylene copolymer (A) and the propylene polymer (B) is 100 mass%); (X1-3) A 1-butene polymer composition having a 1-butene-ethylene copolymer (A) content in the range of 1 to 50 mass%, a propylene polymer (B) content in the range of 30 to 98 mass%, and an ethylene polymer (C) content in the range of 1 to 20 mass% (wherein the total of the 1-butene-ethylene copolymer (A), the propylene polymer (B), and the ethylene polymer (C) is 100 mass%). [Requirement (X1-1)] The content of the 1-butene-ethylene copolymer (A) is preferably in the range of 63 to 99% by mass, and the content of the propylene polymer (B) is in the range of 1 to 37% by mass (wherein the total of the 1-butene-ethylene copolymer (A) and the propylene polymer (B) is 100% by mass). Further, the content of the 1-butene-ethylene copolymer (A) is more preferably in the range of 63 to 97% by mass, and the content of the propylene polymer (B) is more preferably in the range of 3 to 37% by mass, the content of the 1-butene-ethylene copolymer (A) is further preferably in the range of 65 to 95% by mass, and the content of the propylene polymer (B) is further preferably in the range of 5 to 35% by mass, and the content of the 1-butene-ethylene copolymer (A) is particularly preferably in the range of 71 to 95% by mass, and the content of the propylene polymer (B) is particularly preferably in the range of 5 to 29% by mass.

[0085] The 1-butene polymer composition containing the 1-butene-ethylene copolymer (A) and the propylene polymer (B) in the above ranges has good compatibility between the 1-butene-ethylene copolymer (A) and the propylene polymer (B), has heat resistance, and promotes crystallization. The 1-butene-ethylene copolymer composition mainly contains the 1-butene-ethylene copolymer (A), and while retaining the characteristic of the 1-butene-ethylene copolymer (A) being slow in crystallization, the crystallization is promoted by the propylene polymer (B), improving cuttability during pelletization and making it easy to handle as pellets.

[0086] For example, in the case of a hot melt adhesive, when the content of the 1-butene-ethylene copolymer (A) in the 1-butene polymer composition (X) is equal to or higher than the lower limit, the flexibility of the adhesive is excellent, and the adhesive has excellent flexibility and surface conformability, and the open time is long. When the content is equal to or lower than the upper limit, the composition has excellent mechanical strength and heat resistance, and the adhesive strength and creep resistance at high temperatures of the obtained adhesive are improved.

[0087] Furthermore, for example, the fact that the 1-butene polymer composition (X) can be handled as pellets contributes to its use as a modifier for various molded articles in a general-purpose molding machine. When used as a modifier, when the content of the 1-butene-ethylene copolymer (A) in the 1-butene polymer composition (X) is equal to or higher than the lower limit, the composition is excellent in modifying properties such as flexibility and whitening resistance during stretching. When the content is equal to or lower than the upper limit, the composition is easily pelletized and has improved mechanical strength and heat resistance. [Requirement (X1-2)] It is preferable that the content of the 1-butene-ethylene copolymer (A) is in the range of 1 to 62 mass%, and the content of the propylene polymer (B) is in the range of 38 to 99 mass% (wherein the total of the 1-butene-ethylene copolymer (A) and the propylene polymer (B) is 100 mass%), and more preferably that the content of the 1-butene-ethylene copolymer (A) is in the range of 3 to 60 mass%, and the content of the propylene polymer (B) is in the range of 40 to 97 mass%, further preferably that the content of the 1-butene-ethylene copolymer (A) is in the range of 5 to 55 mass%, and the content of the propylene polymer (B) is in the range of 45 to 95 mass%, and particularly preferably that the content of the 1-butene-ethylene copolymer (A) is in the range of 5 to 50 mass%, and the content of the propylene polymer (B) is in the range of 50 to 95 mass%.

[0088] In addition, when the content of the 1-butene-ethylene copolymer (A) in the 1-butene polymer composition (X) in the molded product is within the above range, the mechanical strength (bending resistance, breakage resistance, etc.) of the propylene polymer (B) is improved. point While taking advantage of its characteristics such as strength, heat resistance, etc., the 1-butene-ethylene copolymer (A) makes it easy to obtain molded products that are moderately flexible and have excellent impact resistance, transparency, and whitening resistance when stretched. [Requirement (X1-3)] In the case of a 1-butene polymer composition having three components, 1-butene-ethylene copolymer (A), propylene polymer (B), and ethylene polymer (C), It is preferable that the content of the 1-butene-ethylene copolymer (A) is in the range of 1 to 50 mass%, the content of the propylene polymer (B) is in the range of 30 to 98 mass%, and the content of the ethylene polymer (C) is in the range of 1 to 20 mass% (wherein the total of the 1-butene-ethylene copolymer (A), the propylene polymer (B), and the ethylene polymer (C) is 100 mass%); More preferably, the content of the 1-butene-ethylene copolymer (A) is in the range of 5 to 40% by mass, the content of the propylene polymer (B) is in the range of 42 to 92% by mass, and the content of the ethylene polymer (C) is in the range of 3 to 18% by mass. It is more preferable that the content of the 1-butene-ethylene copolymer (A) is in the range of 8 to 35 mass%, the content of the propylene polymer (B) is in the range of 48 to 88 mass%, and the content of the ethylene polymer (C) is in the range of 4 to 17 mass%.

[0089] In addition, when the content of the 1-butene-ethylene copolymer (A) in the 1-butene polymer composition (X) in the molded product is within the above range, the mechanical strength (bending resistance, breakage resistance, etc.) of the propylene polymer (B) is improved. point While taking advantage of the characteristics of the propylene polymer (B), such as strength, heat resistance, etc., the 1-butene-ethylene copolymer (A) and the ethylene polymer (C) can easily produce molded products that are moderately flexible and have excellent impact resistance and whitening resistance during stretching. In particular, the ethylene polymer (C) has a lower glass transition temperature than the propylene polymer (B), which not only improves impact resistance at low temperatures but also contributes to improved moldability. [Requirements (X2)] Using a differential scanning calorimeter (DSC), the sample was heated from -70°C to 200°C at a heating rate of 20°C / min (first heating), held at 200°C for 10 minutes, then cooled to -70°C at a cooling rate of 20°C / min (first cooling), held at -70°C for 1 minute, and then heated again from -70°C to 200°C at a heating rate of 20°C / min (second heating). In this measurement, the high-temperature peak (crystallization temperature) generated during the first cooling was in the range of 40°C or higher and lower than 110°C, and the first peak (melting peak) generated during the second heating was in the range of 20°C or higher and lower than 100°C, and the second peak (melting peak) was in the range of 100°C to 170°C.

[0090] The 1-butene polymer composition of the present invention preferably has at least a first melting peak and a second melting peak in a differential scanning calorimeter (DSC) curve measured in the second temperature rise.

[0091] Here, the first peak refers to a peak in the DSC curve that is in the range of less than 100° C. The upper limit of the first peak is preferably less than 100° C., more preferably 80° C. or less, and even more preferably 70° C. or less. On the other hand, the lower limit of the first peak is preferably 20° C. or more, more preferably 25° C. or more, and even more preferably 30° C. or more.

[0092] The first peak is a melting peak due to the 1-butene-ethylene copolymer (A). Two or more first peaks may be present. In other words, there may be two or more melting peaks in the range below 100°C.

[0093] The second peak refers to a peak in the range of 100° C. or higher. The upper limit of the second peak is preferably 170° C. or lower, more preferably 168° C. or lower, and even more preferably 165° C. or lower. On the other hand, the lower limit of the second peak is preferably 100° C. or higher, more preferably 105° C. or higher, and even more preferably 110° C. or higher.

[0094] The second peak is a melting peak due to the propylene polymer (B). Two or more second peaks may be present. That is, two or more melting peaks may be present in the range of 100° C. or higher.

[0095] The reason why a melting peak derived from a 1-butene polymer, which is not observed in the 1-butene-ethylene copolymer (A) of the present invention, is observed in the 1-butene polymer composition of the present invention is not necessarily clear. However, it is considered that the 1-butene-ethylene copolymer (A) has a good compatibility with the propylene polymer (B) contained in the ethylene-1-butene polymer composition by appropriately controlling the constitutional units derived from ethylene, and the inclusion of a small amount of propylene polymer (B) promotes crystallization of the 1-butene-ethylene copolymer (A). [Requirement (X3)] The Shore A hardness measured in accordance with ASTM D2240 is preferably in the range of 65-99, more preferably 70-99, further preferably 71-98, and more preferably 72-97. [Requirements (X4)] The Shore D hardness measured in accordance with ASTM D2240 is preferably 20 to 80.

[0096] When the Shore A hardness or Shore D hardness is equal to or less than the upper limit, the crystallinity is low, the flexibility is excellent, and the flexibility and deformation followability as a hot melt adhesive are improved. When the melting enthalpy is equal to or more than the lower limit, the mechanical properties are excellent. When used as a hot melt adhesive, the adhesive strength is improved.

[0097] When flexibility is particularly required, the Shore D hardness is preferably 20-70, and more preferably 20-43. In addition, when excellent mechanical properties are required, the Shore D hardness is preferably 44-80, and more preferably 44-70.

[0098] The 1-butene polymer composition of the present invention has a melt flow rate (MFR) measured in accordance with ASTM D1238 at 190°C under a load of 2.16 kg. Although there are no particular limitations on the MFR, it is preferably in the range of, for example, 0.1 to 100 g / 10 min.

[0099] When the MFR is equal to or higher than the lower limit, the 1-butene polymer composition of the present invention has flowability, and the hot melt adhesive containing the 1-butene polymer composition of the present invention has good handleability and is suitable for high-speed application. When the MFR is equal to or lower than the upper limit, the 1-butene polymer composition of the present invention has excellent mechanical strength and good pelletizing properties. The excellent mechanical strength improves the adhesive strength as a hot melt adhesive and improves the durability as a packaging material. When the MFR is equal to or higher than the lower limit, the 1-butene polymer composition of the present invention has excellent flowability and good application properties as a hot melt adhesive, and various molded articles can be easily formed.

[0100] In particular, when fluidity is required, the MFR is preferably 12 to 100 g / 10 min, and more preferably 12 to 50 g / 10 min. When excellent mechanical strength is required, the MFR is preferably 1 g / 10 min or more and less than 12 g / 10 min. The 1-butene polymer composition of the present invention has a melting enthalpy ΔH at the second peak measured during the second heating period by a differential scanning calorimeter (DSC) of 5 to 100 J / g, preferably 5 to 90 J / g, more preferably 5 to 85 J / g, and further preferably 5 to 80 J / g.

[0101] The fusion enthalpy is an index of the degree of crystallinity. When the fusion enthalpy is below the upper limit, it is easy to obtain a molded product with low crystallinity and excellent flexibility. When used as a hot melt adhesive, it improves flexibility and deformation followability. When the fusion enthalpy is above the lower limit, it is easy to obtain a molded product with excellent mechanical properties and heat resistance. When used as a hot melt adhesive, it improves adhesive strength and creep resistance at high temperatures.

[0102] In the hot melt adhesive, the 1-butene polymer composition of the present invention has a haze of 50% or less, preferably 45% or less, measured in accordance with JIS K 7136. When the haze of the 1-butene polymer composition is within the above range, the composition has good transparency and is suitable as an adhesive or packaging material for applications requiring design.

[0103] To the 1-butene polymer composition of the present invention, at least one additive selected from conventionally known flowability modifiers, crystal nucleating agents, antioxidants, heat stabilizers, weather resistance stabilizers such as ultraviolet absorbers and light stabilizers, hydrochloric acid absorbers, pigments, dyes, antibacterial agents, antifungal agents, antistatic agents, lubricants, slip agents, antiblocking agents, antifogging agents, foaming agents, foaming assistants, plasticizers such as mineral oil, and fillers may be added, if necessary, within a range that does not impair the object of the present invention.

[0104] [Method for producing 1-butene polymer composition] The method for producing the 1-butene polymer composition of the present invention is not particularly limited, and for example, the 1-butene-ethylene copolymer (A) of the present invention, the propylene polymer (B), and optionally the ethylene polymer (C), and optionally other optional components can be mixed in the above-mentioned mixing ratio using, for example, a Henschel mixer, a V-blender, a ribbon blender, a tumbler blender, a kneader-ruder, etc., or the like, after mixing or without mixing, by melt kneading the mixture using a single-screw extruder, a twin-screw extruder, a kneader, a Banbury mixer, etc. Furthermore, granulation, pulverization, etc. may be carried out as necessary.

[0105] When mixing or kneading these components, each component may be added at once or in stages. The method of melt kneading is not particularly limited, and can be carried out using a melt kneading device such as a commercially available extruder. For example, the temperature of the part where kneading is carried out in the melt kneading device is usually 120 to 250° C., preferably 120 to 230° C. The kneading time is usually 0.5 to 30 minutes, particularly preferably 0.5 to 5 minutes.

[0106] [Molded body] Various molded articles formed from the 1-butene-ethylene copolymer (A), the 1-butene polymer composition containing the 1-butene-ethylene copolymer (A) and the propylene polymer (B), or the 1-butene polymer composition containing the 1-butene-ethylene copolymer (A), the propylene polymer (B) and the ethylene polymer (C) of the present invention can be widely used in conventionally known polyolefin applications. The molded articles can be obtained by known thermoforming methods such as extrusion molding, injection molding, inflation molding, blow molding, extrusion blow molding, injection blow molding, press molding, vacuum molding, powder slush molding, calendar molding, and foam molding.

[0107] [Application] The 1-butene-ethylene copolymer (A), the 1-butene polymer composition containing the 1-butene-ethylene copolymer (A) and the propylene polymer (B), or the 1-butene polymer composition containing the 1-butene-ethylene copolymer (A), the propylene polymer (B) and the ethylene polymer (C) of the present invention can be suitably used for pellets and hot melt adhesives, and the hot melt adhesives can be used for automobile parts such as automobile interior parts and exterior parts. In addition, molded articles containing the 1-butene polymer composition can be used for automobile parts such as films, sheets, packaging materials using them, nonwoven fabrics, and automobile interior parts and exterior parts.

[0108] [Preparation and use of hot melt adhesives] The hot melt adhesive of the present invention can be obtained, for example, by melt mixing each component in a melt dissolving tank such as a heated melt stirring tank, preferably under vacuum or nitrogen gas flow, by rotating a stirring blade, in order, by melt mixing by applying a shear under heating with the twin rotating blades of a kneader, or by melt mixing with the screw of a single-screw or twin-screw extruder. The temperature is usually adjusted to 120 to 230°C, preferably 150 to 200°C. The veil-shaped or pellet-shaped sample thus prepared can be used for various purposes.

[0109] In the case of a hot melt adhesive, the adherends may be attached before the adhesive hardens, but the hot melt adhesive that has been hardened may also be heated again to activate it, and then the adherends may be attached. Examples of the shape of the hot melt adhesive itself that has been hardened include a sheet, a film, a nonwoven fabric, a small piece, and a rod.

[0110] In the hot melt adhesive of the present invention, the content of the 1-butene-ethylene copolymer (A) is usually 1 to 90 mass%, preferably 3 to 50 mass%, more preferably 5 to 40 mass%, based on the total mass of the adhesive. A content within the above range is preferable from the viewpoint of the balance between the adhesive strength and coatability of the hot melt adhesive.

[0111] The hot melt adhesive of the present invention may contain a non-crystalline polyalphaolefin (hereinafter, referred to as APAO) as necessary. The melt viscosity of the APAO is preferably 500 to 200,000 mPa·s / 190° C., and more preferably 1,000 to 50,000 mPa·s / 190° C. In other words, if the melt viscosity is less than 500 mPa·s / 190° C., sufficient cohesive force cannot be obtained and the adhesive strength of the adhesive decreases, while if it exceeds 200,000 mPa·s / 190° C., the workability decreases when applying the hot melt adhesive.

[0112] There are various compositions of such APAOs, and some examples include homopolymers or copolymers such as atactic polypropylene and atactic polybutene-1, copolymers or terpolymers of propylene, ethylene, butene-1, etc., propylene homopolymers, propylene-butene copolymers, propylene-ethylene copolymers, etc.

[0113] The 1-butene-ethylene copolymer (A) of the present invention contains a large amount of 1-butene as a constituent unit and has excellent compatibility with propylene-based polymers, and therefore has excellent compatibility with APAOs using propylene or 1-butene, and is preferably used.

[0114] Specific examples of APAO include RT2730 (product name, manufactured by Rextac, melt viscosity at 190°C: 4,000 mPa·s) and VESTOPLAST 704 (product name, manufactured by Evonik, melt viscosity (190°C): 3,500 mPa·s).

[0115] The APAO may be used alone or in combination of two or more kinds. In the hot melt adhesive of the present invention, the content of APAO, when used, is usually 1 to 99 mass %, preferably 10 to 90 mass %, and more preferably 20 to 80 mass %, based on the total amount of the adhesive. A content within the above range is preferable from the viewpoint of the balance between the adhesive strength and coatability of the hot melt adhesive.

[0116] The hot melt adhesive of the present invention may contain a tackifier as required. Examples of the tackifier include at least one resin selected from natural rosin, modified rosin, polyterpene resin, synthetic petroleum resin, coumarone resin, phenol resin, xylene resin, styrene resin, low molecular weight styrene resin, and isoprene resin. Among these, rosin resin, polyterpene resin, and synthetic petroleum resin are preferred, and those having an aliphatic and / or alicyclic structure are more preferred.

[0117] Particularly preferred examples of the petroleum resins having an aliphatic and / or alicyclic structure include partially and completely hydrogenated rosin and derivatives thereof in the case of rosin-based resins, homopolymers or copolymers of cyclic terpenes in the case of polyterpene-based resins, and aliphatic petroleum resins, alicyclic petroleum resins, aliphatic-alicyclic copolymer resins, and hydrogenated copolymers of naphtha cracked oil and various terpenes in the case of synthetic petroleum resins.

[0118] The tackifier preferably has a softening point in the range of 25 to 160° C. A softening point of 25° C. or higher can prevent bleeding onto the surface, while a softening point of 160° C. or lower can provide good processability without excessively high viscosity during melting. Specifically, products under the trade names "Alcon P-70", "Alcon P-90", "Alcon P-100", "Alcon P-115", "Alcon P-125" and "Alcon P-140" (all manufactured by Arakawa Chemical Industries, Ltd.) are preferably used.

[0119] The tackifier may be used alone or in combination of two or more kinds. In the hot melt adhesive of the present invention, when a tackifier is used, the content thereof is usually 1 to 70 mass %, preferably 5 to 50 mass %, and more preferably 10 to 40 mass %, based on the total amount of the adhesive. If the content is within the above range, it is preferable because it is possible to impart fluidity and adhesive power without reducing the adhesive strength.

[0120] The hot melt adhesive of the present invention may contain a wax, if necessary. Examples of the wax include synthetic waxes such as Fischer-Tropsch wax, polyethylene wax, and polypropylene wax, petroleum waxes such as paraffin wax and microcrystalline wax, and natural waxes such as Japan wax, carnauba wax, and beeswax. The 1-butene-ethylene copolymer (A) of the present invention has excellent compatibility with polypropylene, and therefore polypropylene wax is particularly preferred.

[0121] The wax has a Brookfield viscosity (190° C.) of preferably 10 to 8000 mPa·s, more preferably 100 to 5000 mPa·s. If the Brookfield viscosity is within the above range, it is preferable in terms of cohesive force and kneading processability.

[0122] The wax has a melting point measured by DSC of preferably 80 to 150° C., more preferably 90 to 140° C. A melting point within the above range is preferable in terms of flexibility and kneading processability when using the adhesive.

[0123] Examples of commercially available wax products include "Mitsui Hiwax 420P", "Mitsui Hiwax NL100", and "Mitsui Hiwax NP015" (all manufactured by Mitsui Chemicals, Inc.).

[0124] The wax may be used alone or in combination of two or more kinds. In the hot melt adhesive of the present invention, when a wax is used, the content thereof is usually 1 to 60 mass %, preferably 1 to 50 mass %, and more preferably 1 to 40 mass %, based on the total amount of the adhesive. If the content is within the above range, it is preferable because it is possible to impart flowability and heat resistance without reducing adhesive strength.

[0125] If necessary, at least one additive selected from conventionally known flow modifiers, nucleating agents, antioxidants, heat stabilizers, UV absorbers, light stabilizers, pigments, dyes, antibacterial agents, antifungal agents, antistatic agents, foaming agents, foaming assistants, plasticizers such as mineral oil, and fillers can be added to the hot melt adhesive of the present invention, within a range that does not impair the object of the present invention.

[0126] The application of the hot melt adhesive is not particularly limited as long as the object of the present invention can be achieved, but commercially available hot melt applicators are widely used. Examples of types of hot melt applicators include slot coater application, roll coater application, spiral application that can apply in a spiral shape, omega application and control seam application that can apply in a wave shape, slot spray application and curtain spray application that can apply in a planar shape, dot application that can apply in a dot shape, and bead application that can apply in a line shape. A particularly preferred application of the hot melt adhesive is adhesion between cardboard boxes.

[0127] As a method for using the hot melt adhesive of the present invention as a hot melt adhesive, the obtained hot melt adhesive is molded into a sheet, film or nonwoven fabric by a screw extruder having a die part called a T-die method, inflation method, calendar method or spinning method, fixed in the middle of the adherends to be laminated and heat-bonded, or the adhesive molded into a sheet is heated and melted on one adherend and the other adherend is pressed while cooling. In addition, there is a method in which the hot melt adhesive of the present invention is melted by the above-mentioned screw extruder, and the adhesive is directly inserted between the adherends to be laminated without the above-mentioned molding process, and when one adherend is a thermoplastic plastic, it is directly bonded by co-extrusion, or it is directly applied to one adherend and heat-bonded again.

[0128] The hot melt adhesive of the present invention can be suitably used for bonding, for example, between substrates made of polyolefin resins or the like, between the substrates and metal materials (e.g., metal plates, metal foils, metal meshes) or other materials (e.g., nonwoven fabrics, woven fabrics, cloth, paper such as cardboard, glass), and between the metal materials or the other materials themselves, among which it can be particularly suitably used for bonding cardboard and other adherends, or cardboard and cardboard.

[0129] Examples of the substrate made of the polyolefin resin or the like include single-layer or laminated resin sheets of polyolefin resin (e.g., polyethylene, polypropylene), polyester resin, polycarbonate resin, polyarylate resin, acrylic resin, polyphenylene sulfide resin, polystyrene resin, vinyl resin, vinyl chloride resin, polyimide resin, epoxy resin, etc. 〔film〕 The film containing the 1-butene-ethylene copolymer (A) of the present invention or a 1-butene polymer composition using the same may be either a stretched film or a non-stretched film, but is preferably a non-stretched film.

[0130] The non-stretched film is not particularly limited as long as it is a non-stretched film, and the shape, size (thickness), etc. may be appropriately selected according to the desired application. The non-stretched film may be a single layer or a multilayer. When it is a multilayer film, at least one of the layers may be a film containing 1-butene-ethylene copolymer (A) or the present composition. This includes a method of co-extrusion by a known multilayer film forming method such as a T-die film forming method or an inflation film forming method, and a method in which a layer containing 1-butene-ethylene copolymer (A) or the present composition is further laminated on a previously formed substrate. The substrate is not particularly limited, and may be a metal such as an aluminum plate, a steel plate, or a stainless steel plate, or may be a thermoplastic resin. When the non-stretched film is a multilayer film, all of the layers are not stretched.

[0131] The thickness of the unstretched film (total thickness if multi-layered) is preferably 5 μm or more, more preferably 10 μm or more, and is preferably 150 μm or less, more preferably 100 μm or less.

[0132] In this specification, no particular distinction is made between film and sheet, but a film generally refers to a membranous body having a thickness of less than 250 μm, and a sheet generally refers to a thin plate-like body having a thickness of 250 μm or more.

[0133] Specific applications of the non-stretched film include, for example, packaging films for packaging foods, liquids, medicines, etc., and packaging materials obtained therefrom. <Sheet> The sheet is not particularly limited, and the shape, size (thickness), etc. may be appropriately selected according to the desired application. The sheet may be a single layer or a multilayer. When the sheet is a multilayer, at least one layer of the sheet may contain the copolymer (A) or the present composition.

[0134] The thickness of the sheet (if it is multi-layered, the total thickness) is preferably 250 to 2000 μm, more preferably 250 to 1500 μm. Specific uses of the sheet include, for example, packaging sheets for packaging food, liquids, medicines, etc., and containers formed from the sheet (e.g., trays, cups, and containers formed by folding the sheet). EXAMPLES

[0135] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way. The polymers and the like used in the examples and comparative examples are shown below.

[0136] [1-butene-ethylene copolymer (A)] The 1-butene-ethylene copolymers (A-1) to (A-8) obtained in the production examples described below were used.

[0137] As a comparative example, a 1-butene-ethylene copolymer (A'-10) having the physical properties shown in Table 1 was used. [Propylene-based polymer (B)] (B-1): Random polypropylene (manufactured by Prime Polymer Co., Ltd., product name Prime Polypro F327, MFR (230°C, 2.16 kg load): 7g / 10min, melting point: 140°C, mmmm: 95.3%) (B-2): Propylene homopolymer (manufactured by Prime Polymer Co., Ltd., trade name Prime Polypro F107A, MFR (230°C, 2.16 kg load): 7g / 10 min, melting point: 160°C, mmmm fraction: 96%) [Ethylene-based polymer (C)] (C1-1): Low-density polyethylene (manufactured by Mitsui Dow Polychemicals, trade name Mirason 11P, MFR (190°C, 2.16 kg load) 7.2 g / 10 min, density: 0.917 g / cm 3 ) (C2-1); Ethylene-propylene copolymer (MFR (190°C, 2.16 kg load): 0.6 g / 10 min, density: 0.869 g / cm 3 ) [Other ingredients] (PER-1); propylene-ethylene copolymer (manufactured by ExxonMobil Corporation, trade name Vistamaxx3980FL, ethylene content 9 mol%, MFR (230°C, 2.16 kg load): 9 g / 10 min) (PER-2); propylene-ethylene copolymer (manufactured by ExxonMobil Corporation, trade name Vistamaxx3000, ethylene content 11 mol%, MFR (230°C, 2.16 kg load): 7 g / 10 min) [Production example of 1-butene-ethylene copolymer (A)] [Production Example 1] To one of the supply ports of a 300-liter continuous polymerization reactor, n-hexane was supplied at a rate of 14.2 L / h, and from the other supply port, a mixed hexane solution of isopropyldene(3-tert-butyl-5-methylcyclopentadienyl-fluorenyl)zirconium dichloride (main catalyst 1), modified methylaluminoxane, and triisobutylaluminum (main catalyst 1) with a zirconium equivalent concentration of 0.5 mmol / L, modified methylaluminoxane with an aluminum equivalent concentration of 4 mmol / L, and triisobutylaluminum with an aluminum equivalent concentration of 100 mmol / L) was continuously supplied at a rate of 0.22 L / h (total hexane: 10 L / h). At the same time, 1-butene was continuously fed at a rate of 23.5 kg / h, ethylene at 0.39 kg / h, and hydrogen at 4 NL / h from another feed port of the polymerization reactor, and continuous solution polymerization was carried out under the conditions of a polymerization temperature of 60°C, a polymerization pressure of 0.8 MPaG, and a residence time of 1.5 hours, to obtain 1-butene-ethylene copolymer (A-1).

[0138] [Production Examples 2 to 8] 1-Butene-ethylene copolymers (A-2) to (A-8) were produced in the same manner as in Example 1, except that the amounts of 1-butene, ethylene, and hydrogen supplied and the polymerization pressure were adjusted as shown in Table 1.

[0139] The physical properties of the 1-butene-ethylene copolymer (A) and the 1-butene polymer compositions obtained in the Production Examples and Comparative Examples were measured by the following methods. The results are shown in Table 1.

[0140] [Table 1] [1-butene and ethylene content in 1-butene-ethylene copolymer (A)] The 1-butene and ethylene contents were quantified using a Bruker Biospin AVANCE cryo-500 nuclear magnetic resonance spectrometer as follows: the solvent was a mixture of o-dichlorobenzene and deuterated benzene (volume ratio: 80 / 20), the sample concentration was 20 mg / 0.6 mL, the measurement temperature was 120 °C, and the observation angle was 1. 13 C (125 MHz), sequence was single pulse proton broadband decoupling, pulse width was 4.7 μs (45° pulse), repetition time was 5.5 s, number of accumulations was 128, and the chemical shift reference value was the carbon signal of the butene side chain methylene group at 27.50 ppm. 13 The compositions of 1-butene (C4 content; mol%) and ethylene (C2 content; mol%) were quantified by C-NMR spectrum.

[0141] [MFR of 1-butene-ethylene copolymer (A)] The MFR was measured at 190°C and a load of 2.16 kg in accordance with ASTM D1238.

[0142] [Measurement of isotactic pendant fraction (mmmm)] The pentad isotacticity (mmmm) of 1-butene-ethylene copolymer (A) was calculated by the following formula, assuming that the chemical shift of the peak top attributable to the pentad represented by mmmm is 27.5 ppm, by calculating the peak area S with the peak top at 27.5 ppm and the total area S' of the peaks appearing in the range from 27.3 ppm to 26.3 ppm. (Detection limit: 0.01%) (mmmm) = S / (S+S') x 100(%) Here, the main peaks appearing in the range from 27.3 ppm to 26.3 ppm are those assigned to mmmr (27.3 ppm), mmrr and rmr (27.2 ppm), and mrrm (26.3 ppm).

[0143] [Intrinsic viscosity [η](dl / g)] The value of 1-butene-ethylene copolymer (A) was measured in decalin solvent at 135℃ using an Ubbelohde viscometer. Approximately 20mg of the polymer powder, pellets, or resin block was collected and dissolved in 15mL of decalin, and the specific viscosity ηsp was measured in an oil bath heated to 135℃. After diluting the decalin solution by adding 5mL of decalin solvent, the specific viscosity ηsp was measured in the same manner. This dilution procedure was repeated two more times, and the value of ηsp / C when the concentration (C) was extrapolated to zero was calculated as the limiting viscosity [η].

[0144] [η]=lim(ηsp / C) (C→0) [Weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn)] As the GPC device, a Waters gel permeation chromatograph Alliance GPC-2000 was used, and polystyrene-equivalent Mw and Mn were measured under the following conditions, and Mw / Mn was calculated.

[0145] Separation columns: 2 TSKgel GNH6-HT columns manufactured by Tosoh Corporation, and 2 TSKgel GNH6-HTL columns manufactured by Tosoh Corporation (both columns have a diameter of 7.5 mm and a length of 300 mm) Column temperature: 140℃ Mobile phase: o-dichlorobenzene (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) containing 0.025 wt% BHT (manufactured by Takeda Pharmaceutical Co., Ltd.) as an antioxidant. Travel speed: 1.0mL / min Sample concentration: 15mg / 10mL Sample injection volume: 400 μL Detector: Differential refractometer Standard polystyrene: molecular weight Mw<1000 and Mw>4×10 6 In this case, use a product manufactured by Tosoh Corporation, and the molecular weight is 1000≦Mw≦4×10 6 In this case, a product manufactured by Pressure Chemical Co. was used.

[0146] [Melting point and enthalpy of fusion] The melting point and melting enthalpy ΔHfus (1st, 2nd) were measured by the above-mentioned measurement method.

[0147] In the calorimetry of the 1-butene polymer composition using a differential scanning calorimeter (DSC), the melting point and melting enthalpy derived from the 1-butene / ethylene copolymer (A) measured in the first heating rise are referred to as "melting point (1st)_C4", the melting point and melting enthalpy derived from the 1-butene / ethylene copolymer (A) measured in the second heating rise are referred to as "melting point (2nd)_C4", the melting enthalpy and melting enthalpy derived from the propylene polymer (B) measured in the second heating rise are referred to as "melting point (2nd)_PP", and the melting enthalpy and melting enthalpy derived from the propylene polymer (B) measured in the second heating rise are referred to as "melting point (2nd)_PP". <Crystallization temperature and crystallization enthalpy> In addition, the crystallization temperature and crystallization enthalpy derived from the propylene polymer (B) measured at the first temperature drop in the calorimetry of the 1-butene polymer composition using a differential scanning calorimeter (DSC) were defined as "crystallization temperature_PP" and "crystallization enthalpy_PP", respectively.

[0148] [Press molding conditions] The press sheets prepared under the following conditions were used for the tests (hereinafter referred to as test pieces for mechanical properties) which were stored at room temperature for 10 days or more for Production Examples 1 to 4, Production Examples 7 to 8, and Comparative Example 1, and for 15 days or more for Production Examples 5 to 6.

[0149] Press machine: Kansai Roll Co., Ltd. (Model number: PEWE-70 / 50 35) Preheat time: 4 min Preheat and press temperature: 120℃ Pressure: 10MPa Pressurization time: 3 min Cooling rate: 40℃ / min (pressurize to room temperature for 4 minutes at 10MPa using another press set at 20℃) [Crystallization half time (sec)] The crystallization half-time of 1-butene-ethylene copolymer (A) was measured by differential scanning calorimetry (DSC) using a Perkin-Elmer DSC8500. The copolymer was annealed at 200°C for 10 minutes, cooled to a specified temperature (30°C) at a rate of 500°C / min, and the crystallization half-time was measured.

[0150] [Mechanical properties (room temperature)] The mechanical property test pieces were measured for yield stress, breaking strength (TS), breaking elongation (between chucks, EL), and Young's modulus (YM) in accordance with JIS K 6251 (measurement temperature 23°C, tensile speed = 200 mm / min, maximum strain = 800%). For those that did not break at strain = 800%, the stress at this time was recorded as TS.

[0151] [Shore A hardness (instantaneous value) and Shore D hardness] The 1-butene-ethylene copolymer (A) and the 1-butene polymer composition (X) were heated for 4 minutes using a hydraulic hot press molding machine set at 190°C, molded for 3 minutes under a pressure of 10 MPa, and then cooled for 4 minutes at 20°C under a pressure of 10 MPa to prepare a 2 mm-thick sheet (test piece).

[0152] For Production Examples 1 to 4, 7 and 8, and Comparative Example 1, the Shore A and Shore D were measured after storage at room temperature for 10 days or more after molding, and for Production Examples 5 and 6, the Shore A and Shore D were measured after storage at room temperature for 15 days or more after molding. Using an A-type measuring instrument, the scale was read immediately after the indenter touched the test piece, and this was taken as the Shore A hardness (in accordance with ASTM D2240).

[0153] Using a D-type measuring instrument, the indenter was brought into contact with the test piece, and the maximum value was read off to determine the Shore D hardness (in accordance with ASTM D2240). In addition, a 100 μm-thick release PET film (manufactured by Toray, product name: Lumirror) was used as a release film during press molding.

[0154] [Haze (transparency)] In accordance with JIS K 7136, a 2 mm thick sheet obtained by press molding was used to measure the haze with a digital turbidity meter "NDH-20D" manufactured by Nippon Denshoku Industries Co., Ltd.

[0155] Example 1 The 1-butene-ethylene copolymer (A-1) obtained in Production Example 1 was press-molded by the method described above, and the physical properties of the obtained molded product were measured by the methods described above.

[0156] The results are shown in Table 2. [Examples 2 to 15, Comparative Example 1] Using a Labo Plastomill (manufactured by Toyo Seiki Seisakusho, Ltd.), the polymers were kneaded for 5 minutes at 200° C. and 40 rpm in the ratios (mass%) shown in Table 2 to obtain 1-butene polymer compositions. The obtained compositions were press-molded by the method described above, and the physical properties of the obtained molded bodies were measured by the methods described above.

[0157] The results are shown in Table 2.

[0158] [Table 2] The components used in Examples 16, 17 and Comparative Example 2 are shown below.

[0159] [Tackifier] Alicyclic saturated hydrocarbon resin: Arakawa Chemical Industries Co., Ltd. Product name: Alcon P-115 [Base polymer (Z)] Base polymer (Z1): Rextac Co., Ltd., product name RT2730 (melt viscosity at 190°C: 4,000 mPa·s) [Antioxidants] Phenolic antioxidant: Ciba Specialty Chemicals, product name Irganox 1010 The hot melt adhesive compositions used in Examples 16 and 17 and Comparative Example 2 were evaluated by the following methods.

[0160] [Test piece preparation method] The hot melt adhesive composition was placed in a tank using a hot melt glue gun (TR-60LCD) manufactured by REKA Klebetechnik, and melted at 180° C. for 10 minutes or more.

[0161] [Adhesive strength] The obtained hot melt adhesive composition was applied in a bead shape to a polypropylene sheet having a thickness of 400 μm, and after a predetermined time (1 min / 10 min) had elapsed at room temperature, the sheets were laminated together, and a load of 400 g was applied for one day to bond the polypropylene sheets together. The laminated sheets were then cut into strips having a width of 15 mm to prepare test pieces. The test pieces were subjected to a T-peel test at a measurement temperature of 23° C., and the adhesive strength was measured (tensile speed: 50 mm / min). [Adhesive area] The area of ​​the portion of the test piece prepared by the above method where the adhesive and the polypropylene sheet were in close contact was taken as the adhesion area.

[0162] [Open Time] The open time was evaluated based on the adhesion area and adhesion strength retention of the test pieces for which the adhesive strength was measured. The retention rate was calculated based on the adhesion area and adhesion strength of the test pieces bonded together 1 minute and 10 minutes after application, using formula (1).

[0163] a: Adhesive area (adhesive strength) of the test piece bonded 1 minute after application b: Adhesive area (adhesive strength) of test pieces bonded together 10 minutes after application (Formula 1): Retention rate=b / a×100 [%] [B type viscosity (180℃)] The Brookfield Brookfield viscosity at 180° C. was measured using a Brookfield Brookfield viscometer (DVII+PRO RV).

[0164] [Softening temperature (ring and ball method)] The hot melt adhesive composition was melted using an iron plate heated to 230° C., and then cooled and pressed for 5 minutes to produce a disk-shaped pressed sheet.

[0165] The softening temperature of this sample was measured by the ring and ball method using a softening temperature measuring device (ASP-MG type) manufactured by Meitec Corporation. [Examples 16 and 17, Comparative Example 2] APAO-1, ​​antioxidant, 1-butene polymer compositions (Examples 3 and 8), and tackifier in the proportions shown in Table 3 were added to a 500 mL separable flask in that order while checking that each resin was completely melted. The system was stirred with an anchor-shaped stirring blade under a nitrogen atmosphere at a heating temperature of 200°C, a kneading time of 40 minutes (kneading started when APAO was added to the system), and a stirring speed of 10 to 200 rpm, to obtain a hot melt adhesive composition.

[0166] The resulting hot melt adhesive compositions were evaluated by the methods described above. The results are shown in Table 3.

[0167] [Table 3] Press molding was performed by the method described above, and the physical properties of the obtained molded body were measured by the methods described above.

[0168] The results are shown in Table 2. [Examples 18 to 27 and Comparative Examples 3 to 4] The polymers shown in Table 4 were kneaded for 5 minutes at 200° C. and 40 rpm in the ratios (mass%) shown in Table 4 using a Labo Plastomill (manufactured by Toyo Seiki Seisakusho, Ltd.) to obtain 1-butene polymer compositions. The obtained compositions were press-molded by the methods described above, and the physical properties of the obtained molded bodies were measured by the methods described above. <Whitening resistance test> The obtained composition was heated for 5 minutes using a hydraulic heat press molding machine set at 190 ° C, molded for 2 minutes under a pressure of 10 MPa, and then cooled for 4 minutes at 20 ° C and a pressure of 10 MPa to produce a sheet with a thickness of 500 μm. From the sheet, a No. 2 dumbbell as specified in JIS K 6251 was produced, and the hue before stretching (L value (before stretching)) and the hue when stretched 15 mm at a tensile speed of 50 mm / min (L value (after stretching)) were measured using a spectrophotometer (Konica Minolta, Inc., CM-3700d), and the hue change (ΔL) was calculated based on the following formula. In addition, the obtained sheet was heat-treated at 85 ° C for 5 days, and the hue change (ΔL) was calculated in the same manner using the sheet. The smaller the ΔL value, the better the whitening resistance. The results are shown in Table 4.

[0169] ΔL = L value (after stretching) - L value (before stretching)

[0170] [Table 4] [Examples 28 to 35] Except for using raw materials in the proportions (parts by weight) shown in Table 5, the same procedure as in Example 18 was followed as in Example 18, and the materials were kneaded at 200° C. and 40 rpm for 5 minutes using a Labo Plastomill (manufactured by Toyo Seiki Seisakusho, Ltd.) to obtain a 1-butene polymer composition.

[0171] The resulting composition was press-molded by the method described above, and the physical properties of the resulting molded product were measured in the same manner as in Example 18 by the methods described above. The results are shown in Tables 5-1 and 5-2.

[0172] [Comparative Examples 5 to 6] Except for using raw materials in the proportions (parts by weight) shown in Table 5, the same procedure as in Example 18 was followed as in Example 18, and the mixture was kneaded at 200°C and 40 rpm for 5 minutes using a Labo Plastomill (manufactured by Toyo Seiki Seisakusho, Ltd.) to obtain a propylene-based polymer composition.

[0173] The resulting composition was press-molded by the method described above, and the physical properties of the resulting molded product were measured in the same manner as in Example 18 by the methods described above. The results are shown in Tables 5-1 and 5-2. <Melting point and enthalpy of fusion> The melting point Tm(2nd) and melting enthalpy ΔHfus(2nd) were measured by the above-mentioned measurement method.

[0174] Among the melting peaks measured in the second heating, the strongest melting peak in the temperature range of 70° C. to 170° C. was taken as the melting point Tm(2nd), and the area of ​​the melting peak in the previous temperature range was taken as the melting enthalpy ΔH(2nd). <Crystallization temperature and crystallization enthalpy> The crystallization temperature Tc and the crystallization enthalpy ΔHc were measured by the above-mentioned measuring method. Among the crystallization peaks measured in the first temperature drop in the calorimetry of the 1-butene polymer composition with a differential scanning calorimeter (DSC), the strongest crystallization peak in the temperature range of 50°C to 100°C was determined as the crystallization temperature Tc, and the area of ​​the crystallization peak in the aforementioned temperature range was determined as the crystallization enthalpy ΔHc. <Yield point elongation> The test pieces for mechanical properties were measured for yield point elongation in accordance with JIS K 6251 (measurement temperature: 23° C., tensile speed: 50 mm / min).

[0175] [Table 5-1]

[0176] [Table 5-2] [Examples 36 to 38 and Comparative Examples 7 to 8] The 1-butene polymer compositions (X-2) and (X-14) obtained in Examples 3 and 15 were used, and the raw materials shown in Table 6 were kneaded in the ratios (parts by weight) shown in Table 6 using an extruder (φ40 mm), and the obtained pellets were extruded at 230° C. using a cast film molding machine to produce a 100 μm-thick monolayer unstretched film. The obtained monolayer unstretched film was evaluated as follows.

[0177] The results are shown in Table 6. <Heat seal (HS) strength (before heat treatment)> A test specimen was prepared by stacking, in this order, a 50 μm thick Teflon (registered trademark) sheet, two of the obtained single-layer unstretched films, and another 50 μm thick Teflon (registered trademark) sheet.

[0178] The heat seal bar of a heat seal tester (manufactured by Tester Sangyo Co., Ltd., TB-701B type) was set to a width of 15 mm and a length of 300 mm, the temperature of the lower side of the seal bar was set to 70°C, and the temperature of the upper side of the seal bar was set to 190°C, and the test body was sandwiched between the seal bars and heat sealed for 1.0 second at a pressure of 0.2 MPa. After that, the two Teflon sheets were removed to obtain a laminated film, which was left at 23°C for one day. A 15 mm wide slit was made in the laminated film so as to include the heat-sealed portion, and the non-heat-sealed portion was chucked to a tensile tester (manufactured by Intesco Co., Ltd., IM-20ST). The maximum load was measured when the heat-sealed portion was peeled off in the direction of 180° at a speed of 300 mm / min. This measurement was performed five times, and the average value of the maximum load was taken as the heat seal strength.

[0179] [Table 6]

Claims

1. A 1-butene / ethylene copolymer (A) that satisfies the following requirements (A1) to (A5); (A1) the content of the structural unit (i) derived from 1-butene is in the range of 70 to 99.9 mol %, and the content of the structural unit (ii) derived from ethylene is in the range of 0.1 to 30 mol % (wherein the total of the structural units (i) and (ii) is 100 mol %); (A2) 13 The isotactic pendant fraction (mmmm) calculated by C-NMR is in the range of 80 to 99.9%; (A3) The intrinsic viscosity [η] in decalin solvent at 135° C. is in the range of 0.7 to 1.9 dl / g; (A4) The melt flow rate (MFR) measured in accordance with ASTM D1238 at 190°C under a load of 2.16 kg is in the range of 2 to 100 g / 10 min; (A5) Using a differential scanning calorimeter (DSC), the sample is heated from -70°C to 200°C at a heating rate of 20°C / min (first heating), held at 200°C for 10 minutes, then cooled to -70°C at a cooling rate of 20°C / min (first heating), held at -70°C for 1 minute, and then heated again from -70°C to 200°C at a heating rate of 20°C / min (second heating), and no melting peak is observed during the second heating.

2. The 1-butene / ethylene copolymer (A) according to claim 1, which satisfies any one or more of the following requirements (A6) to (A8): (A6) the weight average molecular weight (Mw) is 100,000 to 400,000; (A7) Shore A hardness measured in accordance with ASTM D2240 is in the range of 81 to 99; (A8) The Shore D hardness measured in accordance with ASTM D2240 is in the range of 31 to 60.

3. A 1-butene polymer composition comprising a 1-butene / ethylene copolymer (A) satisfying the following requirements (A1) to (A5) and a propylene polymer (B) satisfying the following requirements (B1) and (B2), and satisfying the following requirement (X1-2); (A1) the content of the structural unit (i) derived from 1-butene is in the range of 70 to 99.9 mol %, and the content of the structural unit (ii) derived from ethylene is in the range of 0.1 to 30 mol % (wherein the total of the structural units (i) and (ii) is 100 mol %); (A2) 13 The isotactic pendant fraction (mmmm) calculated by C-NMR is in the range of 80 to 99.9%; (A3) The intrinsic viscosity [η] in decalin solvent at 135° C. is in the range of 0.7 to 1.9 dl / g; (A4) The melt flow rate (MFR) measured in accordance with ASTM D1238 at 190°C under a load of 2.16 kg is in the range of 2 to 100 g / 10 min; (A5) Using a differential scanning calorimeter (DSC), the temperature is increased from -70°C to 200°C at a heating rate of 20°C / min (first heating), and then the temperature is decreased to -70°C at a cooling rate of 20°C / min (first heating), and the temperature is decreased to -70°C for 1 minute. After that, the temperature is increased again from -70°C to 200°C at a heating rate of 20°C / min (second heating), and no melting peak is observed during the second heating; (B1) The melting point measured by a differential scanning calorimeter is in the range of 100 to 170°C; (B2) the isotactic pentad fraction is in the range of 90 to 99.9%; (X1-2) The content of the 1-butene-ethylene copolymer (A) is in the range of 62 to 1 mass %, and the content of the propylene polymer (B) is in the range of 38 to 99 mass % (wherein the total of the 1-butene-ethylene copolymer (A) and the propylene polymer (B) is 100 mass %).

4. The 1-butene polymer composition according to claim 3, which satisfies the following requirement (X4): (X4) The Shore D hardness measured in accordance with ASTM D2240 is in the range of 20 to 80.

5. The 1-butene polymer composition according to claim 4, which has a Shore D hardness in the range of 20 to 43 as measured in accordance with ASTM D2240.

6. The 1-butene polymer composition according to claim 4, which has a Shore D hardness in the range of 44 to 80 as measured in accordance with ASTM D2240.

7. The 1-butene polymer composition according to any one of claims 3, 4 and 6, comprising an ethylene polymer (C).

8. The 1-butene polymer composition according to claim 7, wherein the ethylene polymer (C) comprises at least one member selected from the group consisting of high-pressure low-density polyethylene (C1) and ethylene / α-olefin copolymer (C2).

9. The 1-butene polymer composition according to claim 7 or 8, which satisfies the following requirement (X1-3): (X1-3) the content of the 1-butene / ethylene copolymer (A) is 1 to 50 mass%, The content of the propylene polymer (B) is 30 to 98% by mass, The content of the ethylene polymer (C) is 1 to 20 mass%, (The total of the 1-butene-ethylene copolymer (A), the propylene polymer (B), and the ethylene polymer (C) is 100% by mass.)

10. The 1-butene polymer composition according to any one of claims 3 to 9, wherein the 1-butene polymer composition has a melting enthalpy ΔH derived from the propylene polymer (B) measured at a second temperature rise time by a differential scanning calorimeter (DSC) of 5 to 100 J / g.

11. The 1-butene polymer composition according to any one of claims 3 to 10, wherein the 1-butene polymer composition has a haze measured in accordance with JIS K 7136 of 50% or less.

12. The 1-butene polymer composition according to any one of claims 3 to 11, wherein the 1-butene polymer composition has a Shore D hardness in the range of 40 to 80 as measured in accordance with ASTM D2240.

13. A pellet containing the 1-butene-ethylene copolymer (A) according to claim 1 or 2, or a pellet containing the 1-butene polymer composition according to any one of claims 3 to 12.

14. A hot melt adhesive comprising the 1-butene-ethylene copolymer (A) according to claim 1 or 2, or the 1-butene polymer composition according to any one of claims 3 to 12.

15. 15. An automotive part selected from an interior part and an exterior part, comprising the hot melt adhesive of claim 14.

16. A film comprising the 1-butene-ethylene copolymer (A) according to claim 1 or 2, or the 1-butene polymer composition according to any one of claims 3 to 12.

17. A nonwoven fabric comprising the 1-butene-ethylene copolymer (A) according to claim 1 or 2, or the 1-butene polymer composition according to any one of claims 3 to 12.

Citation Information

Patent Citations

  • Butene-1 copolymers and methods for their production

    JP2006508237A

  • Pressure-sensitive adhesive using butene-1 copolymer

    JP2014500340A

  • Polyolefin-based hot melt adhesive composition

    JP2017504667A

  • Polyolefin gasket for closure

    JP2018522784A

  • High OTR films made from homopolymer polypropylene and 1-butene / ethylene copolymer blends

    US20040229064A1

Cited By

  • Sealant resin composition and use of same

    JPWO2024053644A1